Assessment of scope for fish biodiversity conservation in relation to environmental variables at Surajpur Lake, an urban wetland of the Upper Gangetic Plain, Northern India - Ansari, Nasim Ahmad (Indian Journal of Fisheries, 2018)
Surajpur Lake is a prominent wetland site in Upper Gangetic Plain in India known for its rich avifaunal and aquatic biodiversity. The present study was carried out to describe the fish diversity in relation to major hydrological and meteorological parameters in spatio-temporal scales from March 2010 to February 2013. Fish samples were collected together with water quality parameters from three sampling blocks of the Surajpur Lake along with three years of meteorological data. The data were analysed using PAST (version 2.15) software. One-way analysis of variance (ANOVA) was used to compare the data among the blocks and months. The relative abundance and composition of fishes were estimated by catch per unit effort (CPUE) independently for each site and month of sampling. Pearson Product Moment Correlation and Principal Component Analysis (PCA) were performed to check the relationship of fish abundance with environmental variables. During the study period, a total of 185 fishes belonging to 15 species and 10 families were recorded. The fish abundance for each sampling block sharply reduced from November to January and gradually increased from February to May, which suggests that fish fauna of the lake prefer pre-monsoon and post-monsoon period. On the basis of catching/sighting frequency, 7 species were categorised as rare, 2 frequent, 2 common, 3 occasional and one (the banded gaurami Trichogaster fasciata) highly abundant, suggesting less sightings of few species and frequent sightings of one species. The relative abundance of fishes in terms of CPUE was highest during the month of May. The Shannon diversity recorded 2.20 among individuals, 1.82 among species and CPUE, 1.57 in block C, 1.22 in block A and 1.05 in block B. The ANOVA indicated that there was no significant (p>0.05) difference in physico-chemical parameters of water quality among the different blocks and months, whereas meteorological parameters showed significant difference among the months. Correlation and PCA analysis illustrated that environmental variables viz., air temperature, rainfall, humidity, wind speed, water temperature, turbidity and phosphate showed positive relationship whereas pH, dissolved oxygen, total hardness, total alkalinity, chloride, nitrate and iron showed negative correlation with fish communities. Overall, our findings suggest that water temperature and rainfall are the main influential factors for fish species distribution in the Surajpur Lake. Results of the present study could be effectively used for proper management as well as for conservation of piscifauna and aquatic biodiversity of Surajpur wetland.